Transcriptome profile analysis reveals putative molecular mechanisms of 5-aminolevulinic acid toxicity - Menezes, Patricia Regina; Trufen, Carlos Eduardo Madureira; Lichtenstein, Flavio; Pellegrina, Diogo Vieira da Silva; Reis, Eduardo Moraes; Onuki, Janice (Archives of biochemistry and biophysics, 2023)
5-aminolevulinic acid (5-ALA) is the first precursor of the heme biosynthesis pathway, accumulated in acute intermittent porphyria (AIP), an inherited metabolic disease characterized by porphobilinogen deaminase deficiency. An increased incidence of hepatocellular carcinoma (HCC) has been reported as a long-term manifestation in symptomatic AIP patients. 5-ALA is an α-aminoketone prone to oxidation, yielding reactive oxygen species and 4,5-dioxovaleric acid. A high concentration of 5-ALA presents deleterious pro-oxidant potential. It can induce apoptosis, DNA damage, mitochondrial dysfunction, and altered expression of carcinogenesis-related proteins. Several hypotheses of the increased risk of HCC rely on the harmful effect of elevated 5-ALA in the liver of AIP patients, which could promote a pro-carcinogenic environment. We investigated the global transcriptional changes and perturbed molecular pathways in HepG2 cells following exposure to 5-ALA 25 mM for 2 h and 24 h using DNA microarray. Distinct transcriptome profiles were observed. 5-ALA '25 mM-2h' upregulated 10 genes associated with oxidative stress response and carcinogenesis. Enrichment analysis of differentially expressed genes by KEGG, Reactome, MetaCore™, and Gene Ontology, showed that 5-ALA '25 mM-24h' enriched pathways involved in drug detoxification, oxidative stress, DNA damage, cell death/survival, cell cycle, and mitochondria dysfunction corroborating the pro-oxidant properties of 5-ALA. Furthermore, our results disclosed other possible processes such as senescence, immune responses, endoplasmic reticulum stress, and also some putative effectors, such as sequestosome, osteopontin, and lon peptidase 1. This study provided additional knowledge about molecular mechanisms of 5-ALA toxicity which is essential to a deeper understanding of AIP and HCC pathophysiology. Furthermore, our findings can contribute to improving the efficacy of current therapies and the development of novel biomarkers and targets for diagnosis, prognosis, and therapeutic strategies for AHP/AIP and associated HCC.
Keywords: Hepatocellular carcinoma; hepatocelulární karcinom; Porphyria, Acute Intermittent; kyselina aminolevulová; lidé; nádory jater; Carcinoma, Hepatocellular; Reactive Oxygen Species; Carcinogenesis; karcinogeneze; Bioinformatics; Liver Neoplasms; 5-aminolevulinic acid; akutní intermitentní porfyrie; reaktivní formy kyslíku; Aminolevulinic Acid; transkriptom; Transcriptome; Porphyrias; Humans